The Role of the Family Hope Program (PKH) in Improving Community Welfare in Sumber Urip Village, Selupu Rejang District, Rejang Lebong Regency - Dina Febria Puspita; Tamrin Bangsu; Desy Afrita (Jurnal Indonesia Sosial Teknologi, 2024)
This study aims to understand the role of the Family Hope Program (PKH) in improving community welfare in Sumber Urip Village, Selupu Rejang District, Rejang Lebong Regency. This study uses a descriptive qualitative approach with data collection through interviews, observations, and documentation. The results of the study show that PKH has succeeded in increasing the access of the poor to basic services such as education and health. In addition, community participation in this program has also increased from year to year, especially in the field of education. However, several challenges in the implementation of the program still exist, such as inequality in receiving assistance and lack of awareness among beneficiaries. This study provides an overview of the effectiveness of PKH in breaking the chain of poverty and improving community welfare, as well as the factors that affect its success